Medicalization of female life stages: a qualitative research - Gamze Kırlı; Şerife Didem Kaya (BMC Health Services Research)
Abstract Background Medicalization involves treating a normal biological process or behavior as a medical issue. Technological developments and media influence have accelerated the spread of medical discourse. All stages of a woman's life, from adolescence to old age, continue to be the subject of medical intervention. Therefore, it is important to obtain the views of physicians and women to uncover the underlying causes of medicalization. This study explores the realities and experiences surrounding medicalization, focusing on both conceptual insights and lived experiences. While traditional life stages such as menstruation, pregnancy, childbirth, menopause and aging are examined, medicalized practices such as anti-aging procedures, abortion and assisted reproductive technologies are also included. Materials and methods The study employs a phenomenological design, a qualitative research method, and utilizes maximum diversity sampling to ensure a broad range of perspectives. The sample comprises 15 specialist physicians in the field of women’s health in Türkiye and 15 female participants aged 18 and over. Data were collected through in-depth interviews with these participants. Interviews were conducted between September 6, 2021, and December 7, 2022. The data was analyzed using the content analysis method and by the MAXQDA Analytics Pro 2022 program. Results The content analysis revealed findings organized into one main theme, two sub-themes, and sixteen categories. According to physician participants, they view the medicalization of women’s lives as essential and attribute it to factors such as education, socio-cultural structures, societal beauty standards, and social media. In contrast, female participants identify social media as a major driver of medicalization, while also citing health concerns, aesthetic desires, and unnecessary examinations or treatment requests by physicians as contributing factors. Conclusion This study reveals multifaceted reasons for medicalization that affect women’s life stages, and it can be attributed to both doctors and women. It also draws attention to how women’s lives are medicalized through various channels like the health institutions, doctors, pharmaceutical industry, and the media.